MODEL PEMBELAJARAN BAHASA INGGRIS SECARA INDIVIDUAL UNTUK PESERTA DIDIK YANG NON-ENGLISH SPEAKER DI SEKOLAH CHILDREN - Ananda Intan Rahmadani; I Ketut Suardana (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
Education is a shared focus for improving the quality of human resources for national development. This research paper aims to review the learning undertaken during the internship program at the Children's House Cendikia Harapan School. This program lasted three months, teaching students at the Kindergarten and Elementary levels. The learning model employed an individual, one-on-one approach, taking into account the social context. Issues that arose included: not all students could speak English, which made it difficult for them to retell the material discussed in English. Furthermore, changes in students' learning moods prompted educators to seek specific strategies to maintain a stable learning mood and achieve learning outcomes. This learning relates to the development of courses such as Learning, Semiotics, Sociolinguistics, Pragmatics, and Psycholinguistics. This research paper is expected to contribute to the development of linguistics, and its findings can motivate other educators to develop contextual learning models.